Personalized Supervision: Enhancing Supervision Strategies in Dissertation-Based Doctoral Programs - Hansen, Michael A. (European Journal of Social Science Education and Research, 2025)
This study examines mental health and supervision experiences among doctoral researchers at a large public university in Finland, where the dissertation is the predominant degree requirement. Using semi-structured interviews and surveys, the study explores doctoral researchers’ mental health, supervision experiences, and opinions on doctoral training. The findings reveal that 35 percent of respondents reported experiencing imposter syndrome and thoughts of inferiority, with 25 percent indicating these issues worsened since starting their doctoral studies. Burnout was reported by 30 percent of participants, particularly among those balancing research with external employment. While generally satisfied with supervision, respondents identified gaps in career guidance and academic training. Additionally, respondents expressed a desire for more frequent feedback, tailored support, and clearer communication about supervision and dissertation expectations earlier in the process. Supervision agreements were highlighted as a crucial tool for establishing clear expectations and responsibilities, ensuring transparency and accountability in the supervisory relationship. Researchers also highlighted a need for workshops on dissertation writing, grant writing, peer review, job applications, and conference participation due to the absence of a robust curriculum. Overall, the study underscores the importance of personalized supervision to enhance doctoral researchers’ academic success and well-being in dissertation-based doctoral programs.
Keywords: Doctoral Supervision; Doctoral Training; Dissertation Supervision; Thesis Supervision